2008
DOI: 10.1007/s11882-008-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory treatment for dermatomyositis

Abstract: Dermatomyositis and polymyositis are classified as members of idiopathic inflammatory myopathies. It has recently become evident that the pathogenesis of the muscle disease for these two entities is likely not the same. Despite this observation, therapies directed at the muscle disease are similar, although therapy for the skin differs slightly. Corticosteroids remain the initial approach to management. The systemic dose of corticosteroids needed to control the disease, particularly the skin disease, is quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…There have been no reported studies specifically evaluating the effect of AZA on skin disease in DM although anecdotal evidence and case reports suggest that it is relatively ineffective in this regard . Several studies have evaluated this drug for the myopathy in PM and/or DM and demonstrated variable results .…”
Section: Azathioprine (Aza)mentioning
confidence: 99%
“…There have been no reported studies specifically evaluating the effect of AZA on skin disease in DM although anecdotal evidence and case reports suggest that it is relatively ineffective in this regard . Several studies have evaluated this drug for the myopathy in PM and/or DM and demonstrated variable results .…”
Section: Azathioprine (Aza)mentioning
confidence: 99%
“…They also stated that there was no improvement after 6 weeks of treatment with prednisone and methotrexate, while DM improved after withdrawal of adalimumab. However, it requires longer than 6 weeks to assess whether or not treatment with corticosteroids and/or methotrexate will be effective for DM 8 .…”
Section: To the Editormentioning
confidence: 99%